PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER MENGGUNAKAN SOFTWARE INCOMEDIA WEBSITE X5 PADA MATA PELAJARAN FISIKA KELAS X SMA - Adinistul Vegian (Universitas Negeri Padang, 2014)
This study originated from less enthuses physics subjects by students . Students find it difficult to understand the physics of subjects due to the limited information provided by the teacher and the limited learning resources . One way to overcome it by providing learning resources such as books and learning resources from the internet . Currently the use of learning resources on the Internet is still not optimal because there are many websites that speak English . For media it is necessary to develop a learning Indonesian language learning website that is practically used . The use of learning media as a learning resource is expected to complement the existing learning resources and help students learn both at school and outside of school independently. This study aims to produce instructional media using INCOMEDIA Website X5 Software for learning high school physics class X valid and practical . This research is a Research and Development ( R & D). The research object is the use of learning media INCOMEDIA Software Website X5 . Data collection instrument in this study is the validation sheet and sheet practicality for teachers and students. The data analysis technique used is descriptive analysis. The results of the validation of the learning media obtained an average value of 77.9 % with the validator valid category . The results on teacher learning media practicality obtained an average value of 87.2 % to the category of very practical , and the practical results of instructional media on the students as users gained an average value of 83.5 % with a practical category